KETAHANAN GELAS-LIMBAH AKTIVITAS TINGGI HASIL VITRIFIKASI MENGGUNAKAN BOTTOM ASH SEBAGAI GLASSFRITS - Budiarti, Ratna; Purwanto, Purwanto; Martono, Herlan (Universitas Diponegoro, 2012)
Vitrification is considered as the most appropriate technology for HLW treatment. However, it has constraints, those are processability, economic, and durability. The purposes of this study are to examine the composition of materials using bottom ash as an alternative glassfrits for vitrification, to assess waste glass durability of selected glassfrits and analyze the economic advantage of bottom ash utilization as glassfrits. This research was conducted with simulated High Level Waste. Glass–waste was melted at its melting point. Glasses used in the study were borosilicate glass, bottom ash glass, and bottom ash glass added B2O3. Parameters used for selected glassfrits are melting temperature, leaching ratecompressive strength and cost analysis. Selected glassfrits was analyzed using XRD and performed tests to determine the effect of pH on leaching rate. The results indicated that the addition of B2O3 in glass bottom ash reduced the melting temperature. This glass has a density of 2.78 g/cm3 , leaching rate of 6.99 x 10-7. Utilization of bottom ash as a glassfrits can save 75, 34% of cost. The results of XRD analysis explained that the devitrification formed a crystalline of Ca-Fe-Al-S-Si-O, Fe+2Fe2 O4+3, Ca-Mg-Fe-Ti-AlSiO. the influence of pH on the leaching rate showed that the highest leaching rate was at acidic condition Keywords: vitrification, chemical durability, mechanical durability, bottom ash